International legal cooperation in “Lava Jato” Case: a critical analysis based on the diversity of national legal systems - Fábio Ramazzini Bechara; Gianpaolo Poggio Smanio; Karin Bianchini Girardi (Revista Brasileira de Direito Processual Penal, 2019)
This article is focused on analyzing, from the data on international cooperation cases in the "Lava Jato" operation, which variable (s) would have influenced the more proactive position of the countries in the implementation of aid applications, despite the diversity between the legal systems. The hypothesis is that the process of internationalization of human rights in the normative sense, and of the respective thematic agendas, such as money laundering, corruption, organized crime, among others, encouraged the adoption of a normative standard that harmonizes the process of interlocution and understanding between different countries.